Islamic Education and Islamization Channels in Malay Peninsula in 7th-8th Centuries AD - Nurbaiti Nurbaiti; Mundzier Suparta; Muhammad Azwar (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This study aimed to discuss the role of Islamization channels in the process of entry and spread of Islam in Malay Peninsula in seventh to eighth century AD. The research used qualitative method with a descriptive analytical approach. By taking data through interview, journals and textbooks, then conducting a description and analysis of the data, the results showed that the process of Islamization in Malay Peninsula in seventh to eighth centuries AD was carried out through several channels, namely trade, marriage, Sufi, politics, education, and arts. The study also showed that Islamic education functioned as the main channel in the process of Islamization. The role of Islamic education was mainly enhancing Muslims’ understanding about Islam which was implemented informally and non-formally. Informal education occurred through the interaction between the ulama and community carrying out everyday lives; while, nonformal education was conducted by holding learning activities in the mosque through small groups known as halaqah. The study concluded that Islamic education was the main channel of the Islamization process in Malay Peninsula.